2024
DOI: 10.1039/d3qo01651j
|View full text |Cite
|
Sign up to set email alerts
|

N-Aminophthalimide-mediated aerobic deborohydroxylation of boronic acid in air

Tao Chen,
Wenzheng Zhang,
Zhenxing Yan
et al.

Abstract: Using readily available N-aminophthalimide as a mediator to activate molecular oxygen, an efficient and convenient metal-free aerobic deborohydroxylation of boronic acids into phenols and alcohols in air is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Therefore, the synthesis of phenols and their derivatives has been widely studied . With the emergence of more and more efficient methods for the synthesis of arylboronic acids, oxidative hydroxylation of arylboronic acids to synthesize phenols is one of the most important transformations, which has attracted huge attention in the past decade. For example, the use of noble metals and/or stoichiometric amounts of strong oxidants (hydrogen peroxide, PhI­(OAc) 2 , mCPBA, benzoquinone, TBHP, oxone, amine oxide, and NaBO 3 ) effectuated the direct oxidative hydroxylation of arylboronic acids to access phenols and derivatives. In addition, an efficient electrosynthesis of phenols from arylboronic acids has also been developed …”
mentioning
confidence: 99%
“…Therefore, the synthesis of phenols and their derivatives has been widely studied . With the emergence of more and more efficient methods for the synthesis of arylboronic acids, oxidative hydroxylation of arylboronic acids to synthesize phenols is one of the most important transformations, which has attracted huge attention in the past decade. For example, the use of noble metals and/or stoichiometric amounts of strong oxidants (hydrogen peroxide, PhI­(OAc) 2 , mCPBA, benzoquinone, TBHP, oxone, amine oxide, and NaBO 3 ) effectuated the direct oxidative hydroxylation of arylboronic acids to access phenols and derivatives. In addition, an efficient electrosynthesis of phenols from arylboronic acids has also been developed …”
mentioning
confidence: 99%
“…In our research on the oxidation of N -aminophthalimide (NPI), we discovered that N -phenylaminophthalimide (NPPI) can mediate the oxidation of boronic acids and borates to phenols or alcohols under basic and O 2 conditions. Further studies revealed that NPPI can generate phenyl radicals in the presence of a base and O 2 .…”
mentioning
confidence: 99%